Genetic heterogeneity in autosomal recessive hearing loss: a survey of Brazilian families - Antunes, Larissa Nascimento; Dias, Alex Marcel Moreira; Schiavo, Beatriz Cetalle; Mendes, Beatriz C. A.; Bertola, Debora Romeo; Lezirovitz, Karina; Mingroni-Netto, Regina Célia (Frontiers in Genetics, 2024)
Hearing loss is a frequent sensory impairment type in humans, with about 50% of prelingual cases being attributed to genetic factors. Autosomal recessive hearing loss (ARHL) exhibits great locus heterogeneity and is responsible for 70 to 80% of hereditary nonsyndromic cases. A total of 90 unrelated Brazilian individuals were selected for having hearing loss of presumably autosomal recessive inheritance, either born from consanguineous marriages or belonging to families with two or more affected individuals in the sibship and most cases were of normal hearing parents. In all cases, common pathogenic variants in GJB2 (c.35delG), GJB6 [del(GJB6-D13S1830) and del(GJB6-D13S1854)] and MT-RNR1 (m.1555A>G) were discarded and most were previously assessed by complete Sanger sequencing of GJB2. Their genetic material was analyzed through next-generation sequencing, targeting 99 hearing loss-related genes and/or whole exome sequencing. In 32 of the 90 probands (36,7%) causative variants were identified, with autosomal recessive inheritance confirmed in all, except for two cases due to dominant variants (SIX1 and P2RX2). Thirty-nine different causative variants were found in 24 different known hearing loss-associated genes, among which 10 variants are novel, indicating wide genetic heterogeneity in the sample, after exclusion of common pathogenic variants. Despite the genetic heterogeneity, some genes showed greater contribution: GJB2, CDH23, MYO15A, OTOF, and USH2A. The present results confirmed that Next Generation Sequencing is an effective tool for identifying causative variants in autosomal recessive hearing loss. To our knowledge, this is the first report of next-generation sequencing being applied to a large cohort of pedigrees with presumable autosomal recessive hearing loss in Brazil and South America.